PENGARUH SISTEM ANTRIAN DI LOKET PENDAFTARAN RAWAT JALAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS DASAN TAPEN TAHUN 2024 - Hartiwi, Septiani; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Slamet Mardiyanto Rahayu; Fathurrahman (Nusadaya Journal of Multidiciplinary Studies, 2024)
This research is motivated by the increasing number of patient visits to the Dasan Tapen Community Health Center year by year, and the lack of specific research on the influence of the queueing system on patient satisfaction at the health facility. Inefficient queueing systems can cause long waiting times and negatively impact patient satisfaction. Although policies and socialization exist, many patients still do not comply with queueing rules, resulting in service delays and additional administrative burdens for officers. Previous research has also shown low patient satisfaction levels at other health facilities, making this research important to assess the situation at the Dasan Tapen Community Health Center. This study aims to determine the influence of the queueing system at the outpatient registration counter on the satisfaction of general patients at the Dasan Tapen Community Health Center. This research uses a quantitative approach with an associative design. The research sample consisted of 50 respondents selected using accidental sampling. Data were collected through questionnaires and observation. Data analysis uses simple linear regression, beginning with the validity and reliability test of the instrument. The t-test is used to test the significance of the influence of the independent variable (queueing system) on the dependent variable (patient satisfaction). The results of the validity and reliability test show that the research instrument is valid and reliable. Simple linear regression analysis shows a positive and significant influence between the queueing system and patient satisfaction (p < 0.05). A regression coefficient of 0.258 indicates a positive relationship, while an R-square value of 0.275 shows that 27.5% of the variation in patient satisfaction is explained by the queueing system; the rest is influenced by other factors. Respondent characteristics show that the majority of respondents are female and aged 17-25 years, with the highest level of education being high school/equivalent.